Analisis Keragaman Tanaman Sebagai Jasa Lingkungan Pada Lanskap Agroforestri di Daerah Aliran Sungai Krueng Aceh - Zulkifli Aiyub Kadir; Bahagia Bahagia (Jurnal Serambi Engineering, 2019)
Humans have utilized landscape for  produces a diverse character of the wider area of the watershed. Agroforestry is a land management system in addressing the problems that arise due to changes in land use of soil and water conservation. The aim of the study was to analyze plant diversity in agroforestry practices that have services in the Krueng watershed landscape in Aceh watershed. Develop strategies in the Krueng Aceh DAS agroforestry service. This research was conducted in the upper, middle and downstream of the Krueng Aceh watershed, with a rapid method of Agro-Biodiversity Appraisal and SWOT. The results showed that the composition of the vegetation structure found in the study sites tended to vary with the diversity index of agroforestry that was currently in the upstream and middle of the Krueng Aceh watershed. Based on SWOT analysis, internal scores are 2.45 and external scores are 3.21. Agroforestry practices in the upper stream of Krueng Aceh watershed were dominated by Aleurites moluccana, Areca cathecu, and  Averrhoa bilimbi L  species with the highest INP in the upper stream of Krueng Aceh watershed. Vegetation at the middle stream of Krueng Aceh watershed dominated by Areca cathecu, Lansium domesticum and Musa paradisiaca.